PENGARUH TOTAL ASSET TURN OVER DAN DEBT TO EQUITY RATIO TERHADAP NET PROFIT MARGIN PADA PT. INDUSTRI JAMU DAN FARMASI SIDO MUNCUL Tbk PERIODE 2014-2024 - Sindi Pebiyani; Hendri Prasetyo (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The purpose of this study is to examine the effect of Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) on Net Profit Margin (NPM) at PT Industri Jamu dan Farmasi Sido Muncul Tbk for the period 2014–2024, both partially and simultaneously. This study employs a quantitative approach using secondary data in the form of balance sheet and income statement reports. The analytical methods applied include multiple linear regression, t-test, and F-test with the assistance of SPSS version 25. The results indicate that TATO and DER each have a positive and significant effect on NPM, with a significance value of 0.001 < 0.05. Simultaneously, both variables are also found to have a significant effect on NPM, with an F-value of 77.214 > F-table 4.46 and a significance level of 0.000 < 0.05. These findings demonstrate that TATO and DER contribute positively to NPM.